Predicting the transmissibility of a glove material to the palm using a simple lumped parameter model of the hand and the glove - Md Rezali, Khairil Anas; As'arry, Azizan; Zulkefli, Zamir Aimaduddin; Samin, Razali; Abdul Jalil, Nawal Aswan (Universiti Teknologi Malaysia Press, 2016)
Assessing a glove for its ability to reduce vibration transmitted to the hand can be improved if the transmissibility of the glove to the hand can be predicted. This study proposes a simple lumped parameter model of the hand and the glove for predicting the transmissibility of a glove to the hand. The model of the hand consists of three main body segments: the palm, the fingers, and the palm tissues, connected via translational and rotational springs and dampers. The glove material was represented by translational spring and damper. The results showed that the glove transmissibility predicted using the model overestimated the glove transmissibility measured experimentally at frequencies greater than 62 Hz, implying that a simple three degree-of-freedom model of the hand and the glove may not be able to provide a reasonable prediction of glove transmissibility.